Pengaruh Transformational Leadership terhadap Affective Organizational Commitment dan Job Performance dimediasi oleh Employee Engagement pada PT. XYZ - Neman, Edith Maryane Irma; Hosen, Chandra (Universitas Bunda Mulia, 2024)
Currently many employees of productive age are changing jobs, this is a challenge for leaders to manage and retain quality employees so they can continue to develop their potential. This research is a quamtitative study that has 33 samples through the distribution of questionnaires conducted, with measurements using a Likert scale of 1-7 for the questionnaire. A type of desctivtive research that explains the relationship between each variable. Then data processing with PLS-SEM and using measurement model analysis and structural models. The result of the study with the aim of examining the influence of transformational leadership on affective organizational commitment and job performance mediated by employee engagement, which then resulted that transformational leadership was able to have a positive impact on affective organizational commitment and job performance through mediation carried out by the employee engagement variable. Transformational leadership itself also directly positively affects affective commitment, but cannot have a direct positive impact on job performance. These finding prove the importance of strengthening employee engagement to increase affective organizational commitment and job performance among employees in a company.